THE ROLE OF RELIGION IN THE EMERGENCE AND RESOLUTION OF CONFLICT: A PSYCHOLOGICAL APPROACH (Web of Teachers: Inderscience Research, 2026)
Conflict in societies arises as a natural and inevitable part of human relationships. This article analyzes the psychological role of religion in both the emergence and resolution of conflicts. The impact of religion on individual and social peace is examined, emphasizing the role of values such as empathy, forgiveness, patience, and justice in conflict resolution. By integrating psychological and theological approaches, the study aims to reveal the potential of religion to build peace. Furthermore, within the framework of the "religious coping" concept in modern psychology literature, the role of religion in regulating emotions such as stress, fear, and anger is evaluated.